Pectin-assisted dispersion of exfoliated boron nitride nanosheets for assembled bio-composite aerogels. (April 2019) - Yang, Wei; Yuen, Anthony Chun Yin; Ping, Peng; Wei, Rui-Chao; Hua, Lei; Zhu, Zheng; Li, Ao; Zhu, San-E; Wang, Li-Li; Liang, Jing; Chen, Timothy Bo Yuan; Yu, Bin; et al.
Graphical abstract: Abstract: Boron nitride nanosheets (BNNSs) were prepared via the exfoliation of hexagonal boron nitride in isopropyl alcohol. Extremely stable BNNSs dispersions were obtained after the ultrasonication in pectin aqueous suspensions, and the bio-composite aerogels were fabricated via the freeze-drying process. The digital photographs of pectin/BNNSs aqueous suspensions and Fourier-transform infrared spectroscopy results showed that there was a strong interfacial interaction between BNNSs and pectin macromolecular chains. Owing to the excellent dispersion and intensive interaction, the thermal stability, compressive strength and flame retardant properties of pectin/BNNSs bio-composite aerogels were significantly improved. Compared to neat pectin aerogel, pectin/BNNSs-2 (mass ratio of pectin and BNNSs, 10/1) possessed improved onset thermal decomposition temperature (by 9 °C), enhanced compressive strength (by 119%), reduced peak heat release rate (by 45%) and peak CO2 production (by 53%) at cone radiation intensity of 60 kW/m 2 . Residue analysis indicated that the presence of BNNSs promoted the carbonization of pectin aerogels.